Thermo-Mechanical Analysis in the Fresh Fruit Cold Chain: A Review on Recent Advances - Alemayehu Ambaw; Tobi Fadiji; Umezuruike Linus Opara (Foods, 2021)
In agro-food research and industry, mathematical models are being used to develop and optimize preharvest and postharvest operations, and their use has grown exponentially over the last decade. Generally, transport phenomena (such as airflow, heat, and mass transfer) during the cooling of horticultural products are complex; therefore, the use of computational modeling techniques is a valid alternative to expensive and difficult experiments because computers continuously become more powerful and less expensive, the software is readily available, and once a model is validated, it is a versatile tool to evaluate the effects of the operating and design parameters involved. In this review, thermo-mechanical modeling studies during postharvest handling are overviewed regarding the experimental, analytical, and computational approaches. The airflow, cooling kinetics, cooling uniformity, and the material and mechanical safety behavior of fresh fruit packaging boxes will be analyzed. Current concerns, challenges, and opportunities are discussed.